PENGARUH KEPEMIMPINAN, KOMPETENSI, DAN PELATIHAN TERHADAP KINERJA PEGAWAI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN SOPPENG - Sunarti Sunarti; Rasyid Rasyid; Gunawan BI (STIE AMKOP, 2017)
Abstract Sunarti, Effect of Leadership, Competence and Training on Employee Performance Parts General Regional Secretariat Soppeng. This research aims: 1) To determine and analyze the effect on employee performance leadership of General Affairs Regional Secretariat Soppeng; 2) To know and analyze the effect on employee performance competence of the General Section Regional Secretariat Soppeng; 3) To know and analyze the impact of training on employee performance General Affairs Regional Secretariat Soppeng; 4) To know and analyze the influence of leadership, competence and training simultaneously on employee performance General Affairs Regional Secretariat Soppeng. The research was conducted at the General Secretariat of the Regional Section Soppeng. The population in this study were all employees at the General Affairs Regional Secretariat Soppeng as many as 37 employees. Given the relatively small number of the population, so the sample is determined by using census method. Analysis of the data in this study using multiple linear regression analysis. The results showed that: 1) Leadership positive and significant effect on the performance of employees of the General Section Regional Secretariat Soppeng. 2) Competence positive and significant effect on the performance of employees of the General Section Regional Secretariat Soppeng. 3) Training and significant positive effect on employee performance General Affairs Regional Secretariat Soppeng. 4) Leadership, competence and training simultaneously significant effect on employee performance General Affairs Regional Secretariat Soppeng. Keywords: Leadership, Competencies, Training, Employee Performance.